2022
DOI: 10.3390/app12199560
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Electroencephalogram (qEEG) as a Natural and Non-Invasive Window into Living Brain and Mind in the Functional Continuum of Healthy and Pathological Conditions

Abstract: Many practicing clinicians are time-poor and are unaware of the accumulated neuroscience developments. Additionally, given the conservative nature of their field, key insights and findings trickle through into the mainstream clinical zeitgeist rather slowly. Over many decades, clinical, systemic, and cognitive neuroscience have produced a large and diverse body of evidence for the potential utility of brain activity (measured by electroencephalogram—EEG) for neurology and psychiatry. Unfortunately, these data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 616 publications
0
3
0
Order By: Relevance
“…We believe that by using tests with different methodological approaches (neuropsychological analysis and qEEG) we can better characterize the dysfunction of the brain system. On one hand, the use of qEEG is economical, fast, reproducible, and yields precise data in neurology and psychiatry that can be compared over time [ 56 ]. In line with previous observations [ 14 , 15 , 16 ], we observed that the QEEG data (delta and theta bands and their spatial distribution) allow a distinction between FTD, AD, and healthy aging controls.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that by using tests with different methodological approaches (neuropsychological analysis and qEEG) we can better characterize the dysfunction of the brain system. On one hand, the use of qEEG is economical, fast, reproducible, and yields precise data in neurology and psychiatry that can be compared over time [ 56 ]. In line with previous observations [ 14 , 15 , 16 ], we observed that the QEEG data (delta and theta bands and their spatial distribution) allow a distinction between FTD, AD, and healthy aging controls.…”
Section: Discussionmentioning
confidence: 99%
“…Now that we have this overview in place, we can move on to the topic of our analysis. Next, we will advance the analysis of these three phenomena (described by three concepts above; Figure 1) by exploring in more detail their neurophenomenology and mutual relationship within the common conceptual framework (Operational Architectonics [24,25]) stemming from the advanced analysis of the EEG neuroimaging technique [89][90][91]. Operational, in this context, refers to the notion of 'operation', which is both a process lasting in time and simultaneously an event that has a beginning and an end [24,25].…”
Section: Neurophenomenology Of Non- Un- and Sub-consciousnessmentioning
confidence: 99%
“…Several fundamental steps and techniques are used in this process to identify the physiological dysfunctions of human bodies. Electroencephalogram or EEG is one of the most influential tools used in the diagnosis of cardiac disorders or muscle movement misbalancing along with abnormal neural activities [8]. ECG is another initial cardiac dysfunction identification method under biomedical signal processing that helps to classify the signals along with analysing the signal to take preventive measures.…”
Section: Evaluation Of Trends Of Biomedical Signal Processingmentioning
confidence: 99%